Caper (Capparis spinosa L.): An Updated Review on Its Phytochemistry, Nutritional Value, Traditional Uses, and Therapeutic Potential - Annaz, Hassan; Sane, Yaya; Bitchagno, Gabin Thierry M.; Ben Bakrim, Widad; Drissi, Badreddine; Mahdi, Ismail; El Bouhssini, Mustapha; Sobeh, Mansour (Frontiers in Pharmacology, 2022)
Caper (Capparis spinosa L.) is a perennial shrub of the family Capparaceae, endemic to circum-Mediterranean countries. Caper carries a renown nutritional value especially in term of vitamins and antioxidants related to the occurrence of flavonoids, alkaloids, and glucosinolates as main secondary metabolites. Caper extracts have also shown to display antibacterial, antifungal, analgesic, anti-tumor, hepatoprotective, antioxidant, anti-inflammatory and neuroprotective effects which correlate the uses of the plant in folk medicine against both metabolic and infectious diseases. The present review aimed to provide exhaustive phytochemistry and pharmacological properties survey on Caper constituents. Attention has been also given to the nutritional values and traditional uses of main organs to pinpoint research gaps for future investigations on the plant.